PENGARUH PERLINDUNGAN HUKUM BAGI CORPORATE GUARANTEE SEBAGAI AKIBAT WANPRESTASI DEBITOR DALAM PEMBIAYAAN BANK - Andari Yurikosari; Ani Wijayati; Erna Sari (Fakultas Hukum Universitas Kristen Indonesia, 2021)
This study aims to determine the effect of legal protection for Corporate Guarantee as a result of default by debtors in providing bank credit, to study if the voluntary corporate guarantor legal protection relinquishes the privilege to act as a corporate guarantee in a bankruptcy case, and how the legal protection of creditors who hold a corporate guarantee in terms of bankrupt debtor. This type of research is normative-empirical law using statutory and conceptual and sociological approaches based on the Theory of Justice and Theory of Legal Certainty. Primary, secondary and tertiary legal materials using qualitative analysis. Regulations regarding legal protection for corporate guarantees in credit agreements with individual guarantees are regulated in Law Number 10 of 1998 concerning Banking, the legal protection provided by creditors according to the Banking Law. Kata kunci : Perlindungan Hukum, Corporate Guarantee, Pembiayaan Bank